2012
DOI: 10.3389/fnana.2012.00008
|View full text |Cite
|
Sign up to set email alerts
|

An agonist–antagonist cerebellar nuclear system controlling eyelid kinematics during motor learning

Abstract: The presence of two antagonistic groups of deep cerebellar nuclei neurons has been reported as necessary for a proper dynamic control of learned motor responses. Most models of cerebellar function seem to ignore the biomechanical need for a double activation–deactivation system controlling eyelid kinematics, since most of them accept that, for closing the eyelid, only the activation of the orbicularis oculi (OO) muscle (via the red nucleus to the facial motor nucleus) is necessary, without a simultaneous deact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…These interactions are modulated by Purkinje cell inhibition. One consequence of this combination of excitation and inhibition of projection neurons could be coordination of the OOM and levator palpebrae allowing closure of the eyelids (Sanchez-Campusano et al, 2012). In the case of eyeblink conditioning, increased Purkinje cells inhibition of the inhibitory interneurons apposing a projection neuron would increase the likelihood of that cell firing and producing a conditioned response.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions are modulated by Purkinje cell inhibition. One consequence of this combination of excitation and inhibition of projection neurons could be coordination of the OOM and levator palpebrae allowing closure of the eyelids (Sanchez-Campusano et al, 2012). In the case of eyeblink conditioning, increased Purkinje cells inhibition of the inhibitory interneurons apposing a projection neuron would increase the likelihood of that cell firing and producing a conditioned response.…”
Section: Discussionmentioning
confidence: 99%
“…Purkinje cells that increase simple spike activity during the CS increase inhibition of the cerebellar deep nuclei and may thereby decrease excitatory output to motor neurons that activate the levator palpebrae. An elegant study by Delgado-Garcia and colleagues found that different classes of neurons in the interpositus nucleus are excited or inhibited during eyeblink conditioning in cats (Sanchez-Campusano, Gruart, Fernandez-Mas, & Delgado-Garcia, 2012). They found that type-A neurons in the interpositus nucleus increase firing during eyelid closure, whereas type-B neurons fire tonically when the eyelid is open and reduce firing when the eyelid is closing.…”
Section: New Perspectives On Cerebellar Plasticity: Purkinje Cell mentioning
confidence: 99%
“…They found that type-A neurons in the interpositus nucleus increase firing during eyelid closure, whereas type-B neurons fire tonically when the eyelid is open and reduce firing when the eyelid is closing. This antagonistic action of the different types of interpositus neurons is thought to be necessary for the normal kinematic properties of the eyelid closure CR (Sanchez-Campusano et al, 2012). What is the mechanism underlying the pause in type-B neuron activity during eyelid movement?…”
Section: New Perspectives On Cerebellar Plasticity: Purkinje Cell mentioning
confidence: 99%
“…Actually, recent reviews were published trying to get a consensus about the functional complexity that links the cerebellar intrinsic and extrinsic circuits with the motor coordination and learning; to conclude that there is still a lot of work to be done to get a precise idea about cerebellar cognitive function and the physiopathology of behavioral deficits in cerebellar dysfunctions (Ito, 2006 , 2008 ; Manto et al, 2012 ). In this book, functional mechanisms of cerebellar circuits involved in motor learning are represented by the contribution of Dr. Jose Maria Delgado-Garcia's group (Sánchez-Campusano et al, 2012 ), where by modern electrophysiological methods they accurately analyzed the role of interpositus neurons in eyelid kinetics, demonstrating that antagonistic groups of deep cerebellar nuclei neurons are required for proper dynamic control of learned motor responses.…”
mentioning
confidence: 99%